2020
DOI: 10.3390/biology9090252
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds in Anti-Diabetic Plants: From Herbal Medicine to Modern Drug Discovery

Abstract: Natural products, including organisms (plants, animals, or microorganisms) have been shown to possess health benefits for animals and humans. According to the estimation of the World Health Organization, in developing countries, 80% of the population has still depended on traditional medicines or folk medicines which are mostly prepared from the plant for prevention or treatment diseases. Traditional medicine from plant extracts has proved to be more affordable, clinically effective and relatively less adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
165
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(172 citation statements)
references
References 147 publications
4
165
0
3
Order By: Relevance
“…Among the isolated compounds, caffeic acid (5), methyl caffeate (6), ferulic acid (7), chlorogenic acid (8), naringenin (11), nicotiflorin (12), and astragalin (13) increased GSIS. Our results are in agreement with previous studies, which showed that caffeic acid (5) [16,17], ferulic acid (7) [18], chlorogenic acid (8), naringenin (11) [17], and astragalin (13) [19] have been reported to increase insulin secretion [20]. Whereas each compound was previously isolated from a different plant, in our study, PRPE with GSIS effect contained all these compounds, with the addition of methyl caffeate (6), chlorogenic acid (8), and nicotiflorin (12), for which no GSIS effect was reported.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Among the isolated compounds, caffeic acid (5), methyl caffeate (6), ferulic acid (7), chlorogenic acid (8), naringenin (11), nicotiflorin (12), and astragalin (13) increased GSIS. Our results are in agreement with previous studies, which showed that caffeic acid (5) [16,17], ferulic acid (7) [18], chlorogenic acid (8), naringenin (11) [17], and astragalin (13) [19] have been reported to increase insulin secretion [20]. Whereas each compound was previously isolated from a different plant, in our study, PRPE with GSIS effect contained all these compounds, with the addition of methyl caffeate (6), chlorogenic acid (8), and nicotiflorin (12), for which no GSIS effect was reported.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, methyl caffeate (6) has a better effect than its free acid form, caffeic acid (5). Several studies on the biological activities of methyl caffeate (6) have reported its neuroprotective [36], anticancer [37], antioxidant [38], and anti-inflammatory effects [39] as well as antimicrobial and antimycobacterial activities [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes mellitus exists as type 1 diabetes, which is caused by failure of pancreas to produce sufficient insulin for the body, and type II diabetes which results from the inability of the body to efficiently utilize insulin leading to enhanced blood glucose concentration in body; complications can result including hypertension, kidney disorder, eye damage, nerve damage, damage to blood vessels, lower lib amputation, heart damage, stroke and blindness 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, for controlling glucose level, the modern medicines recommended for diabetes are classified into six categories (i.e. biguanides (metformin), alpha-glucosidase inhibitors, meglitinides (glinides), sulfonylureas, thiazolidinediones (glitazones), and DPP-4 inhibitors) and two types of injections 4 . However, several side and adverse effects of such medications are known including gastrointestinal disorder, nausea, diarrhea, compromised renal function, de-compensated heart failure, liver disease, weight gain, cardiovascular risks and increased risk of heart attack 5 .…”
Section: Introductionmentioning
confidence: 99%